Porous composite absorbers derived from zinc-iron complexes

Porous composite absorbing materials were prepared by explosive decomposition and high-temperature calcining methods of zinc-iron acetate tetraazole complex, which solved the problem of insufficient absorption performance of existing materials in the low frequency band, and achieved efficient and environmentally friendly electromagnetic wave absorption effect.

CN114364242BActive Publication Date: 2025-04-29ZHONGBEI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111558285.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-18
Publication Date
2025-04-29
Estimated Expiration
2041-12-18

AI Technical Summary

Technical Problem

The existing wave absorbing materials have insufficient electromagnetic wave absorption performance in the low-frequency band, and the preparation process is complex and the environmentally friendly performance is poor, making it difficult to meet the requirements of "strength, wide, thin and light".

Method used

Zinc-iron tetraazole acetate-iron complex is used as the precursor, and nano-scale porous composite absorbing materials are prepared by explosive decomposition and high-temperature calcination, and cured and molded with paraffin to improve the absorbing performance and industrial applicability of the materials.

Benefits of technology

It achieves effective electromagnetic wave absorption of more than 90% in the frequency range of 1.2-18GHz, has low material density, simple and environmentally friendly technology, and is suitable as a high-efficiency electromagnetic radiation absorbing material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114364242B_ABST
    Figure CN114364242B_ABST
Patent Text Reader

Abstract

The present invention provides a porous composite microwave absorber derived from a zinc-iron complex and a preparation method thereof. Using ferric chloride, zinc nitrate, and tetrazole acetic acid as organic ligands and water as a solvent, under the condition of 80-90 oC °, a zinc-iron heteronuclear energetic complex {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} is synthesized. n After it is explosively decomposed in a sealed reaction kettle at 280 oC °, and then calcined in a nitrogen atmosphere at 650 o °C for 2 hours, a nano- and micron-scale composite powder composed of Fe, ZnO, Fe3O4, ZnFe2O4, amorphous carbon, and graphene can be obtained. After this powder is mixed with paraffin in a mass ratio of 7:3, in the range of 1.2-18 GHz and with a thickness between 1-10 mm, there is an effective absorption of more than 90% (≤ -10 dB). Therefore, the obtained composite microwave absorption powder is a potential high-efficiency microwave absorption material both in daily life and in military applications. This preparation method has the characteristics of being green and environmentally friendly and having a simple preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular is a porous wave absorbing material derived from a zinc tetrazolylacetic acid-iron complex and a preparation method thereof. Background Art

[0002] In daily life, the main electromagnetic pollution comes from broadcast transmission systems, radio frequencies and some household appliances, and the operating frequencies of these devices are almost all in the low frequency band of 1-4GHz. The common operating frequency of radar is 2-18GHz. Absorbing materials are functional materials that absorb or weaken electromagnetic waves incident on the surface of the material, thereby reducing electromagnetic radiation. Compared with shielding materials, they can fundamentally eliminate electromagnetic pollution. In order to reduce the harm of electromagnetic radiation to human production and living environment, and to ensure military safety and improve military stealth technology, the development and design of efficient electromagnetic protection materials are of great significance to human health and national defense security.

[0003] Ideal absorbing materials should meet the requirements of "strong, wide, thin, and light". Carbon-based absorbing materials have the advantages of corrosion resistance, high dielectric constant, and low density. However, carbon-based materials are non-magnetic and have high conductivity. When used alone, they have disadvantages such as poor impedance matching, weak absorption intensity, and narrow absorption band. Therefore, carbon materials and magnetic metal materials can be combined to obtain composite materials with both dielectric loss and magnetic loss. Due to the microstructure of the material, such as the porous structure or high porosity inside the material, it will be beneficial to the multiple conduction and dissipation of electromagnetic waves and improve the impedance matching of the material, which can greatly improve the material's absorption. Therefore, the proposed porous composite material is expected to obtain high absorption performance.

[0004] Metal-Organic Frameworks (MOFs) are a type of crystalline porous material with a periodic network structure formed by the self-assembly of inorganic metal centers and bridging organic ligands. MOFs can be used to prepare a porous carbon composite material with an orderly structure after high-temperature calcination, making it an ideal precursor for preparing various functional nanomaterials. Since the real part of the dielectric constant of ZnO is small, but the dielectric loss tangent is large, it has a higher electromagnetic wave attenuation ability; iron oxide or iron has magnetism, so the present invention intends to prepare a metal organic framework compound (MOFs) composed of zinc and iron as a precursor, and obtain a magnetic carbon porous absorbing composite material through a high-temperature pyrolysis strategy.

[0005] Nanomaterials, due to their quantum effects, locality of matter, and huge surface and interface effects, present many strange phenomena and properties that are different from macroscopic objects and single isolated atoms. Nano absorbers have good absorbency and are characterized by light weight, wide bandwidth, good compatibility, and thin thickness. The detonation method is unique among many nanomaterial preparation methods. The chemical reaction of explosive explosion is used to quickly convert chemical energy into thermal energy in a very short explosion moment, and at the same time, a strong shock wave is generated, causing the reactants to gasify or form atomic clusters, molecular clusters, or small mass active groups. During the cooling process, atomic clusters and other active groups interact and precipitate to form materials with nanoscale size and new structures. Tetrazolyl compounds have excellent coordination ability, diverse coordination modes, and a large number of N=N and CN bonds with high formation enthalpy in their structures. They have high energy and are a commonly used energetic ligand. Most of the combustion products are N2, which will not cause pollution. Tetrazolylacetic acid contains carboxyl groups and is a good energetic ligand. In this paper, the zinc-iron heteronuclear energetic complex {[ZnFe3O(tza)6(H2O)3]·(NO3)3·5H2O} was prepared with tetrazolylacetic acid as ligand and zinc and iron as central atoms. n , put it into a small stainless steel explosion-proof reactor with a high temperature resistant, acid and alkali resistant inner tank, decompose the zinc-iron heteronuclear energetic complex explosively at a certain temperature, then cool the decomposition product and place it in a tubular furnace filled with inert gas, calcine it at different temperatures for a certain time, and obtain a series of nano- and micron-level porous composite wave absorbing materials, mix it with paraffin in a certain mass ratio to make a coaxial ring with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of 2.00mm, and test the wave absorbing properties of the material. The results show that the powder obtained by calcining at 650℃ for 2 hours in an inert atmosphere has an effective electromagnetic wave absorption property of more than 90% (reflection loss is less than -10dB) when the filling amount is 70wt%, the thickness of the wave absorbing layer is 1-10mm, and the frequency is 1.2-18GHz, and it is a potential electromagnetic radiation absorbing material for civilian and military use. The synthesis method has the characteristics of mild reaction process, simple and rapid, environmentally friendly and easy to industrialize. Summary of the invention

[0006] In view of the above situation, the purpose of the present invention is to provide a porous absorbing material derived from a zinc-iron tetrazolylacetic acid complex and a preparation method thereof, which has a simple process and is environmentally friendly, can effectively improve the yield, and provide excellent absorbing performance.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is to provide a porous absorbing material derived from zinc-iron tetrazolyl acetate complex and a preparation method thereof, wherein the zinc-iron tetrazolyl energetic complex is used as a precursor, and the powder obtained after explosive decomposition in a closed container is then calcined at different temperatures for a certain period of time in an inert atmosphere to obtain a nano- and micron-level porous composite absorbing material. The implementation process of the present invention is as follows:

[0008] 1. Synthesis of zinc-iron heteronuclear energetic complexes: Dissolve a certain amount of tetrazolylacetic acid and FeCl3·6H2O in 20.0-40.0 ml of distilled water, adjust the pH of the solution to 8.0-9.0 with hydrochloric acid and sodium hydroxide, heat and stir in a constant temperature water bath at 70-90°C for half an hour, add Zn(NO3)3·6H2O in a certain proportion to tetrazolylacetic acid and FeCl3·6H2O, and continue heating and stirring for one hour. Cool the solution to room temperature, filter the filtrate and volatilize it naturally at room temperature. After one week, red-brown block crystals are generated with the molecular formula {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n .

[0009] The above example is only an example of the synthesis of zinc-iron heteronuclear tetrazolylacetic acid complexes by tetrazolylacetic acid, ferric chloride and zinc nitrate. The added metal ions should include corresponding sulfates, acetates, nitrates and carbonates, etc. The concentration range of each reactant can be increased and decreased tenfold, respectively, and the ratio of ligand to each metal ion is 12:1-1:12.

[0010] 2. Heteronuclear energetic complex {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Explosive decomposition: Place the heteronuclear energetic complex in a small stainless steel explosion-proof reactor (inner diameter 40mm, height 90mm, high temperature resistance ≤350℃, high pressure resistance ≤6MPa) with a high temperature, acid and alkali resistant inner tank, then place the container in a muffle furnace and heat it to 280-300℃ to make the zinc-iron heteronuclear energetic complex explode and decompose, cool it to room temperature with the furnace, and then place it in a tubular furnace filled with inert gas and heat it at 5-10℃·min -1 The temperature is raised from room temperature to a lower temperature and calcined for 2-3 hours, and then cooled to room temperature, thereby preparing nano- and micron-sized composite porous absorbing materials.

[0011] 3. Curing and molding: The products calcined at different temperatures are fully mixed with paraffin wax in a certain mass ratio, and then placed in an oven at 80°C and heated for about 20 minutes. After the paraffin wax becomes liquid, take it out and stir it quickly. After the sample solidifies, continue to heat it in an oven at 80°C for 20 minutes, then take it out and continue to stir it evenly. Repeat this three times. The stirred sample is placed in a mold and pressed into a ring with a fixed pressure, and the sample thickness is controlled to 2.000±0.020mm. The electromagnetic parameters are tested with an Agilent E5071C vector network analyzer, and the wave absorption performance is calculated. The test frequency range is 0-18GHz.

[0012] The beneficial effects of the method are as follows: the method utilizes the energetic material explosion method to prepare the porous composite wave-absorbing material, which has the characteristics of high yield, low density, excellent wave-absorbing performance, simple process and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Coordination environment diagram and three-dimensional network diagram a;

[0014] Figure 2 is {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Coordination environment diagram and three-dimensional network diagram b;

[0015] Figure 3 is {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Coordination environment diagram and three-dimensional network diagram c;

[0016] Figure 4 is {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Coordination environment diagram and three-dimensional network diagram d;

[0017] Figure 5 The XRD spectrum of the powder of the explosion decomposition product calcined at 550° C. in a nitrogen atmosphere for 2 h in Example 1;

[0018] Figure 6 Graph a is a curve showing the change of electromagnetic wave reflection loss versus frequency at different thicknesses of the composite absorbing material obtained in Example 1;

[0019] Figure 7 b is a graph showing the variation of the electromagnetic wave reflection loss of the composite absorbing material obtained in Example 1 with the frequency at different thicknesses;

[0020] Figure 8The XRD spectrum of the absorbing powder obtained by calcining at 650°C for 2h in Example 2;

[0021] Fig. 9 Graph a is a curve showing the change of electromagnetic wave reflection loss with frequency at different thicknesses of the composite powder obtained in Example 2; Fig.10 b is a graph showing the variation of electromagnetic wave reflection loss with frequency at different thicknesses of the composite powder obtained in Example 2;

[0022] Fig.11 The XRD pattern of the absorbing powder obtained by calcining at 750°C for 2h in Example 3;

[0023] Fig.12 Graph a is a curve showing the change of electromagnetic wave reflection loss versus frequency at different thicknesses of the composite absorbing material obtained in Example 3;

[0024] Fig.13 b is a graph showing the variation of the electromagnetic wave reflection loss of the composite absorbing material obtained in Example 3 with the frequency at different thicknesses;

[0025] Fig.14 The Raman spectra of the explosive decomposition products of the absorbing powder calcined at 550℃, 650℃ and 750℃ for 2h respectively;

[0026] Fig.15 SEM spectrum of porous absorbing powder calcined at 650℃ for 2h a;

[0027] Fig.16 b is the SEM spectrum of the porous absorbing powder calcined at 650℃ for 2h;

[0028] Fig.17 The dielectric loss and magnetic loss tangent values ​​of the three samples at 550℃ calcination temperature;

[0029] Fig.18 The impedance matching diagram of the three samples calcined at 550℃ varies with frequency;

[0030] Fig.19 The dielectric loss and magnetic loss tangent values ​​of the three samples at 650℃ calcination temperature;

[0031] Fig. 20 The impedance matching of three samples at 650℃ calcination temperature varies with frequency;

[0032] Fig.21 The dielectric loss and magnetic loss tangent values ​​of the three samples at 750℃ calcination temperature;

[0033] Fig. 22 The impedance matching of three samples changes with frequency at 750℃ calcination temperature. DETAILED DESCRIPTION

[0034] Example 1: A composite absorbing material prepared based on zinc tetrazolylacetic acid-iron complex and a preparation method thereof;

[0035] 1. Synthesis of zinc-iron heteronuclear energetic complexes: A certain amount of tetrazolylacetic acid (Htza, 0.1536 g, 1.2 mmol) and FeCl3·6H2O (0.1080 g, 0.4 mmol) were completely dissolved in 30.0 ml of distilled water in sequence, and the pH of the solution was adjusted to 9.0 with hydrochloric acid and sodium hydroxide. The solution was heated and stirred in a constant temperature water bath at 80°C for half an hour. Zn(NO3)3·6H2O (0.1190 g, 0.4 mmol) was added and continued to heat and stir for one hour. The solution was cooled to room temperature and the filtrate was filtered and naturally evaporated at room temperature. After eight days, reddish-brown block crystals were generated with the molecular formula {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n .

[0036] 2. Heteronuclear energetic complex {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Explosive decomposition: The heteronuclear energetic complex (0.5 g) was placed in a small stainless steel explosion-proof reactor, which was placed in a muffle furnace and heated to 280 °C to allow the zinc-iron heteronuclear energetic complex to explode and decompose. The complex was cooled to room temperature and then placed in a nitrogen-filled tubular furnace at 5 °C min -1 The temperature is raised from room temperature to 550°C at a rate of 2h, calcined for 2h, and then cooled to room temperature, thereby preparing nano- and micron-scale composite porous absorbing materials (represented by ZnFe-MOF-550).

[0037] 3. Curing and molding: fully mix the above-obtained product with paraffin wax in a mass ratio of 7:3, and then heat it in an oven at 80°C for about 20 minutes. After the paraffin wax becomes liquid, take it out and stir it quickly. After the sample solidifies, continue to heat it in an oven at 80°C for 20 minutes, then take it out and continue to stir it evenly. Repeat this three times. Put the stirred sample into a mold and press it into a ring with a fixed pressure, and control the sample thickness to 2.000±0.020mm. Test its wave absorption performance.

[0038] Figure 1-4 The complex {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} in Example 1 n The structure of the crystal belongs to the hexagonal P63 / m space group. The asymmetric unit is composed of Zn 2+ and [Fe3O(tza)6] + and composition, such as Figure 1 The structure shown contains: 1 / 6 Zn 2+, 1 / 2 Fe 3+ , 1 / 6 O atom, 1 tza - , 1 / 2 NO3 - , 1 / 2 coordinated H2O and 5 / 6 lattice H2O. Central Zn 2+ The ion is a hexacoordinated octahedral configuration, and the six coordinating atoms are from different ligands tza - The N4 atom on the tetrazole ring The N-Zn-N bond angle ranges from 87.59(11)° to 180.0°, such as Figure 2 ; CenterFe 3+ The ion also has a six-coordinated octahedral geometry, with four of the coordination sites coming from different tza - The carboxyl O atom (O1 vi ,O1 vii ,O2 and O2 viii ), one of the other two coordinations comes from the μ3-O atom (O3), and the other comes from the O atom coordinated to H2O (O4), such as Figure 3 ; The bond angle of O-Fe-O is in the range of 84.04(11)° to 169.80(11)°, and the bond length of Fe-O is arrive In the complex {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n In the three-dimensional network structure, [Fe3O(tza)6] + The cationic unit is composed of three Fe atoms, one μ3-O atom and six tza atoms. - ions. Among them, μ3-O is located at the center of the equilateral triangle formed by three Fe atoms. In addition, [Fe3O(tza)6] + All tza in ions - The ion passes through the N4 atom on the tetrazole ring and Zn 2+ Coordinated, alternately connected to form a three-dimensional zinc-iron heterometallic network structure, Figure 4 It can be seen that the structure has one-dimensional channels.

[0039] Figure 5The diffraction peaks of sample ZnFe-MOF-550 at 2θ=44.8°, 65.2° and 82.5° are consistent with the characteristic diffraction peaks corresponding to the (011), (002) and (112) crystal planes of Fe, indicating the presence of Fe in the product; the diffraction peaks of the sample at 2θ=31.9°, 34.6°, 36.3° and 47.6° are respectively corresponding to the diffraction peaks of the (010), (002), (011) and (012) crystal planes of ZnO, indicating the presence of ZnO in the product; the diffraction peaks at 2θ=30.2°, 35.5°, 57.0° and 62.6° are respectively corresponding to the diffraction peaks of the (011), (002), (011) and (012) crystal planes of ZnO, indicating the presence of ZnO in the product. No.96-900-5840) correspond to the (022), (113), (115), and (044) crystal plane diffraction peaks of Fe3O4, respectively, indicating the presence of Fe3O4 in the product; the diffraction peaks at 2θ=30.2°, 35.5°, and 62.6° correspond to the (022), (113), and (044) crystal plane diffraction peaks of ZnFe2O4, respectively, according to the standard diffraction card of ZnFe2O4 (COD No.96-900-6903), indicating the presence of ZnFe2O4 in the product.

[0040] Raman test was performed on the sample ZnFe-MOF-550, and the results are as follows Figure 8 As shown. 0-750cm -1 The peaks are typical peaks of ZnO nanocrystals and ZnFe2O4 nanoparticles. -1 and 1580cm -1 The characteristic peaks near the carbon material are respectively attributed to the two characteristic peaks D and G, I D / I G The value of is 1.17, which indicates the degree of graphitization. The larger the value, the smaller the degree of graphitization of the sample, and the more amorphous carbon there is in the sample. In summary, the obtained mixture is composed of Fe, ZnO, Fe3O4, ZnFe2O4, amorphous carbon and graphene.

[0041] The curve of reflection loss of porous wave-absorbing powder prepared in Example 1 of the present invention as a function of frequency is shown in FIG. Figure 6 As shown in the figure, when the matching thickness is 2.5mm, the maximum absorption intensity reaches -21.6dB at 8.6GHz, and the effective frequency band (≤-10dB) is as wide as 3.2GHz; Figure 7, the minimum reflection loss at a frequency of 2.7GHz and a matching thickness of 7.0mm can reach -17.1dB. When the thickness is between 1-5.5mm, in the range of 3-18GHz, the nanocomposite powder has an effective absorption of more than 90% (≤-10dB); when the matching thickness is 5-10mm, the nanocomposite powder also has an effective absorption of more than 90% (≤-10dB) in the low frequency range of 1.5-4GHz, so the obtained composite absorbing powder is a potential high-efficiency absorbing material both in daily life and in military use.

[0042] Example 2

[0043] The preparation method and steps of the wave absorbing material based on the zinc-iron tetrazolylacetic acid complex are the same as those in Example 1. The difference between the two is that the calcination temperature in the nitrogen-filled tubular furnace is different. In this example, the calcination temperature is 5°C·min -1 The temperature is raised from room temperature to 650°C at a rate of 100°C, kept at that temperature for 2 hours, and then cooled to room temperature, thereby obtaining a nano- and micron-sized porous composite absorbing material (represented by ZnFe-MOF-650).

[0044] Figure 8 The XRD pattern of the microwave absorbing powder prepared in Example 2 and calcined at 650°C for 2h. Figure 8 It can be seen that the diffraction peaks of ZnFe-MOF-650 at 2θ=44.8°, 65.1° and 82.4° are consistent with the characteristic diffraction peaks corresponding to the (011), (002) and (112) crystal planes of Fe, indicating the presence of Fe in the product; the diffraction peaks at 2θ=35.5°, 57.0° and 62.6° are consistent with the characteristic diffraction peaks corresponding to the (011), (002) and (112) crystal planes of Fe, indicating the presence of Fe in the product; the diffraction peaks at 2θ=34.4° and 62.6° are consistent with the standard diffraction card of ZnO (COD No.96-900-5838), which correspond to the diffraction peaks of the (113), (115) and (044) crystal planes of Fe3O4, respectively, indicating the presence of Fe3O4 in the product; the diffraction peaks at 2θ=34.4° and 62.6° are consistent with the standard diffraction card of ZnO (COD The diffraction peaks at 2θ=35.5°, 44.2° and 65.1° respectively correspond to the diffraction peaks of (113), (004) and (044) of ZnFe2O4 according to the standard diffraction card of ZnFe2O4 (COD No.96-900-4181), which indicate the presence of ZnFe2O4 in the product.

[0045] Depend on Figure 8 As shown, 0-750cm -1The peaks may be attributed to the typical peaks of ZnO nanocrystals and ZnFe2O4 nanoparticles. -1 and 1580cm -1 The characteristic peaks near the carbon material are respectively attributed to the two characteristic peaks D and G, I D / I G The value of is 1.22. The larger the value, the smaller the degree of graphitization of the sample, and the more amorphous carbon there is in the sample. In summary, the main components of the 650℃ calcined product, i.e., the composite material, are Fe, ZnO, Fe3O4, ZnFe2O4, amorphous carbon and graphene.

[0046] Fig. 9 , 10 This is the electromagnetic wave reflection loss spectrum of the ZnFe-MOF-650 derived porous composite absorbing material prepared in Example 2 at different thicknesses. At a thickness of 2.4 mm and a frequency of 8.7 GHz, when the powder mass fraction is 70 wt% after mixing with paraffin, the minimum reflection loss is -37.9 dB, and the effective absorption bandwidth is 3.7 GHz. Fig. 9 As shown; at 2.7GHz and a matching thickness of 6.5mm, the minimum reflection loss can reach -23.2dB. Fig.10 As shown. Between 1-5.5mm, in the range of 2.6-18GHz, the nanocomposite powder has an effective absorption of more than 90% (≤-10dB); when the matching thickness is 4-10mm, the nanocomposite powder also has an effective absorption of more than 90% (≤-10dB) in the low frequency range of 1.2-4GHz. Therefore, the obtained composite absorbing powder has an effective absorption of more than 90% (≤-10dB) in the thickness range of 1-10mm and 1.2-18GHz, so it is a potential high-efficiency radiation protection material both in daily life and in military use.

[0047] Example 3

[0048] The preparation method and steps of the wave absorbing material based on the zinc-iron tetrazolylacetic acid complex are the same as those in Example 1. The main difference is that the calcination temperature in the nitrogen-filled tubular furnace is different. In this example, the calcination temperature is 5°C·min -1 The temperature was raised from room temperature to 750°C at a rate of 100 °C, kept at that temperature for 2 h, and then cooled to room temperature to obtain a nano- and micron-sized porous composite absorbing material (ZnFe-MOF-750).

[0049] Fig.11 It is the XRD pattern of the absorbing powder calcined at 750℃ for 2h. Fig.11It can be seen that the diffraction peaks of ZnFe-MOF-750 at 2θ=44.8°, 65.1° and 82.4° are consistent with the characteristic diffraction peaks corresponding to the (011), (002) and (112) crystal planes of Fe according to the standard diffraction card of Fe (COD No.96-500-0218), indicating the presence of Fe in the product; the diffraction peaks at 2θ=30.1°, 35.5° and 57.0° are consistent with the characteristic diffraction peaks corresponding to the (022), (113) and (115) crystal planes of Fe3O4 according to the standard diffraction card of Fe3O4 (COD No.96-900-7645), indicating the presence of Fe3O4 in the product; the diffraction peaks at 2θ=30.1°, 35.5° and 57.0° are consistent with the characteristic diffraction peaks corresponding to the (011), (002) and (112) crystal planes of Fe according to the standard diffraction card of ZnFe2O4 (COD No.96-900-6896) correspond to the (022), (113), and (115) crystal plane diffraction peaks of ZnFe2O4, indicating the presence of ZnFe2O4 in the product. Fig.14 As shown in Figure 2, the main components of the composite material calcined at 750°C are Fe, Fe3O4, ZnFe2O4, amorphous carbon and graphene.

[0050] Fig.12 , 13 The curve of the electromagnetic wave reflection loss of the composite powder obtained in Example 3 at different thicknesses versus frequency shows that at a thickness of 4.5 mm and a frequency of 1.8 GHz, when the mass fraction of the powder after mixing with paraffin is 70 wt%, the minimum reflection loss is -9.6 dB. Fig.12 ; The minimum reflection loss at a frequency of 1.3GHz and a matching thickness of 10mm can reach -9.3dB. Fig.13 ; This indicates that the powder has poor microwave absorption performance.

[0051] like Fig.17 , 19 , 21, Magnetic tangent loss (tanδ) of ZnFe-MOF-550, ZnFe-MOF-650 and ZnFe-MOF-750 in the frequency range of 0-18.0 GHz μ ) value is higher than the dielectric tangent loss value (tanδ ε ), indicating that the magnetic loss mechanism is dominant. When the impedance of the material surface matches that of free space (the material's intrinsic parameter μ r and ε r Approximately equal), impedance matching value (|Z0 / Z in |) is close to 1.0, the electromagnetic wave can reduce reflection and be absorbed by the material to the maximum extent. Fig.18 , 20, 22 It can be seen that the impedance matching value of ZnFe-MOF-650 is closest to 1, and the impedance matching value of ZnFe-MOF-550 is lower than that of ZnFe-MOF-650, which is about 0.84 (frequency 8.6GHz, matching thickness 2.5mm); while the impedance matching value of sample ZnFe-MOF-750 is the smallest, which is 0.50, and the wave absorption performance is the weakest. Therefore, the powder calcined and kept at 550℃ and 650℃ for 2h in a tubular furnace has the best wave absorption performance. Combined with the above experimental data, in comparison, the ZnFe-MOF-650 composite powder has the best wave absorption performance.

[0052] Fig.15 , 16 This is the SEM spectrum of the absorbing powder calcined at 650℃ for 2h. Fig.15 , 16 It can be seen that the sample after high-temperature calcination at 650℃ for 2h is an aggregate of nano- and micron-sized particles with a bud-like structure and an overall loose and porous structure. This porous structure is conducive to multiple reflections and absorption of incident electromagnetic waves inside the material, which is beneficial to improving the material's wave absorbing performance.

[0053] In summary, when the current body {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n The powder obtained by calcining the explosive decomposition product at a temperature of 650℃ for 2 hours has the widest absorption band and the highest wave absorption intensity. The loss mechanism of the sample ZnFe-MOF-650 may be: first, the three-dimensional porous conductive network prolongs the transmission loss path of the incident electromagnetic wave and produces multiple reflections and scattering, which contributes to the attenuation of the electromagnetic wave. Secondly, the multipolarization process plays an important role in the dissipation of electromagnetic waves. For example, a large number of heterogeneous interfaces between ZnFe2O4 / C / Fe3O4 / Fe and ZnO lead to interface polarization. Under the action of the electric field, the functional group defects in the carbon material and ZnFe2O4 produce dipole polarization; ZnO with a high dielectric constant produces dipole polarization; in addition, the magnetic powders Fe3O4, Fe and ZnFe2O4 mainly produce magnetic losses due to natural resonance, eddy current loss, and exchange resonance, so that the synthesized sample ZnFe-MOF-650 exhibits efficient electromagnetic wave absorption performance.

[0054] In summary, ZnFe-MOF-650 powder shows good absorption in the range of 1-10nm thickness and 1.2-18GHz, so it is a potential high-efficiency electromagnetic wave absorption material both in daily life and in military use.

[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite absorber derived from a zinc tetrazolylacetic acid-iron complex, characterized in that: The composite absorber is composed of Fe, ZnO, Fe3O4, ZnFe2O4, amorphous carbon and graphene. The preparation method of the composite absorber comprises the following steps: Step (1), a certain amount of tetrazolylacetic acid and FeCl3·6H2O are completely dissolved in 20.0-40.0 ml of distilled water in sequence, the pH of the solution is adjusted to 8.0-9.0 with hydrochloric acid and sodium hydroxide, and heated and stirred in a constant temperature water bath of 70-90°C for half an hour, and Zn(NO3)2·6H2O in a certain proportion to tetrazolylacetic acid and FeCl3·6H2O is added, and heating and stirring are continued for one hour, the solution is cooled to room temperature, and the filtrate obtained by filtering is naturally volatilized at room temperature, and reddish brown block crystals are generated after one week, and the molecular formula is: <h2 style=";text-align:left;direction:ltr">{[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O}<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> ; Step (2), {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Place it in a small stainless steel explosion-proof reactor with a high temperature, acid and alkali resistant inner tank, and then put the reactor into a muffle furnace at 5-10℃·min -1 The rate of heating to 280-300 ° C makes {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n Explosive decomposition, stop heating, and cool to room temperature with the furnace; Step (3), after the explosion decomposition product is cooled, it is placed in a tubular furnace filled with inert gas at 5-10℃·min -1 The temperature was raised from room temperature to different temperatures for 2-3 h, and then cooled to room temperature; Step (4), after the products calcined at different temperatures are fully mixed with paraffin in a certain mass ratio, they are placed in an oven at 80°C and heated for about 20 minutes. After the paraffin becomes liquid, they are taken out and quickly stirred evenly. After the sample solidifies, they are placed in an oven at 80°C and heated for 20 minutes, then taken out and stirred evenly. This is repeated three times to obtain a composite absorbing material.

2. The composite absorber according to claim 1, characterized in that: The FeCl3·6H2O and Zn(NO3)2·6H2O in step (1) can be replaced by corresponding sulfates, nitrates, acetates, carbonates and chlorides; the concentration range of each reactant can be increased and decreased tenfold respectively, and the ratio of ligand to each metal ion is 12:1-1:

12.

3. The composite absorber according to claim 1, characterized in that: In step (3), the temperature is raised from room temperature to different temperatures, where the different temperatures are 500-800° C.; the inert gas is nitrogen, argon or a mixture thereof.

Citation Information

Patent Citations

  • Structure having property for conducting or absorbing electromagnetic wave

    CN101164394A

  • Extra-high-pressure-resistant high-temperature-resistant mixed silicone rubber and preparation method thereof

    CN111363365A